APPLICATION OF THE "BRAINSTORMING" METHOD IN TEACHING ANALYTICAL CHEMISTRY TO PHARMACY STUDENTS AT BUKOVINIAN STATE MEDICAL UNIVERSITY - Велика, Алла; Кропельницька, Юлія; Гарвасюк, Олександра (SWorldJournal, 2025)
Modern education in Ukraine is primarily focused on universal human values, specifically on the personality-activity approach. This means that the student is at the centre of the educational process, and their development and formation as a personality oc